2013
DOI: 10.1177/1535370213508360
|View full text |Cite
|
Sign up to set email alerts
|

Fresh onion juice enhanced copulatory behavior in male rats with and without paroxetine-induced sexual dysfunction

Abstract: Onion (Allium cepa) is one of the most commonly cultivated species of the family Liliaceae, and has long been used in dietary and therapeutic applications. Treatment with fresh onion juice has been reported to promote testosterone production in male rats. Testosterone is the male sex hormone responsible for enhancing sexual libido and potency. This study aimed to investigate the effects of onion juice on copulatory behavior of sexually potent male rats and in male rats with paroxetine-induced sexual dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Our study disagrees with weight gain exerted by C. esculentus extract in another study suggesting that the extract may not affect metabolism. 20 This study disagree with the report by Ezeh et al 3 where it was reported that regular consumption of tiger nut tubers is capable of improving appetite. Significant increase in morphometric parameters of the testis and epididymis of treated rats was observed in this study (P < 0.05) compared to the control (Table 3).…”
Section: Resultscontrasting
confidence: 63%
“…Our study disagrees with weight gain exerted by C. esculentus extract in another study suggesting that the extract may not affect metabolism. 20 This study disagree with the report by Ezeh et al 3 where it was reported that regular consumption of tiger nut tubers is capable of improving appetite. Significant increase in morphometric parameters of the testis and epididymis of treated rats was observed in this study (P < 0.05) compared to the control (Table 3).…”
Section: Resultscontrasting
confidence: 63%
“…In addition, an improvement in sexual performance was evidenced in these rats through increased intromission frequency and ratio parameters after tiger nut administration. Intromission frequency reflects the efficient activation of ejaculatory reflexes, while intromission ratio, also known as copulatory efficacy or hit rate, represents the facilitation of erection and penile orientation [ 10 , 13 ]. Both parameters are considered pure measurements of sexual performance in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…A sexually receptive female rat was then introduced into the chamber. The following parameters of sexual behavior were measured as described previously [ 10 , 13 ]: (1) Mount latency: time from introduction of the female until the first mount; (2) intromission latency: time from introduction of the female until the first intromission (vaginal penetration); (3) mount frequency: number of mounts preceding ejaculation; (4) intromission frequency: number of intromissions preceding ejaculation; (5) ejaculation latency: time from the first intromission until ejaculation; (6) post-ejaculatory interval: time from ejaculation until the next intromission; (7) intromission ratio: a measure of intromissive success calculated as intromission frequency/(mount frequency+intromission frequency); and (8) inter-intromission interval: the average interval between successive intromissions calculated as ejaculation latency/intromission frequency. Tests were ended immediately after the first post-ejaculatory intromission.…”
Section: Methodsmentioning
confidence: 99%
“…Paroxetine‐induced sexual dysfunction model was used in the present investigation because of its wide acceptability for studying the potency of medicinal plants and its natural products (Ajiboye, Nurudeen, & Yakubu, ; Allouh, Daradka, Al Barbarawi, & Mustafa, ; Malviya, Jain, Gupta, & Vyas, , ; Sabiu, Ajani, Bamishile, & Yinusa, ). Similarly, Powmax M was also adopted as a positive control in the current investigation because apart from being one of the pharmacologically approved herbal drugs in Nigeria that has brought relief to some of the inhabitants on cases relating to sexual dysfunction, it is a non‐orthodox herbal drug that has been reported to restore all the components of sexual activity in male rats (Ajiboye et al., ; Kayode & Yakubu, ; Sabiu et al., ).…”
Section: Introductionmentioning
confidence: 99%